The Effects of Reimplementing a Biometric Attendance Monitoring System in the Electronics Engineering Department at Don Honorio Ventura State University - Frigillana, Katherine G.; Jocson, Joefil C.; Muldong, Roviel Manfre C.; Natividad, Lester O.; Tiongson, Hazel T. (Engineering And Technology Journal, 2023)
Monitoring the attendance of staff and employees holds paramount importance in organizational settings. This can be accomplished either manually, using logbooks and daily time records, or automatically through advanced technologies such as radio frequency identification, biometrics, and bar code scanners. Biometrics attendance monitoring systems, in particular, offer a range of benefits, including heightened security, accuracy, convenience, scalability, time efficiency, compliance, and accountability. This research paper elucidates the advantages of the biometric system, examining its impact on the employees of the Electronics Engineering Department at Don Honorio Ventura State University during the 1st Semester of the Academic Year 2023-2024. The Biometrics Attendance System proves to be exceptionally effective and efficient, gaining a consensus of 92% among participants regarding its positive impacts. Ratings consistently hover at 4 or 5 for efficiency, underscoring the streamlined processes. Accessibility earns a positive average score of 80%, and privacy measures receive an equally commendable average score of 82%. While the system generally contributes positively to managing absenteeism, an outlier score of 1 from a participant prompts further investigation. In conclusion, the Biometrics Attendance System excels in effectiveness, efficiency, and user satisfaction, positioning itself as a secure, accurate, and convenient solution. This becomes especially relevant as the Electronics Engineering Department integrates the biometric system, reaping benefits in terms of security, accuracy, and time efficiency. However, it’s noteworthy that the implementation of the biometrics attendance system correlates with an increase in faculty absenteeism. Addressing specific concerns identified in the Manual Attendance System could guide targeted improvements for a more comprehensive and satisfactory attendance monitoring system overall.